Kitten's first full moon - Henkes, Kevin ([New York] : Greenwillow Books, 2004)
When Kitten mistakes the full moon for a bowl of milk, she ends up tired, wet, and hungry trying to reach it.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Children.
2.7
K-3
Keywords: Animals -- Infancy -- Juvenile fiction; Cats -- Juvenile fiction; Animals -- Infancy -- Fiction; Cats -- Fiction; Animal babies -- Fiction; Cats -- Fiction; Moon -- Juvenile fiction; Moon -- Fiction; Moon -- Fiction